THE INFLUENCE OF TRUST, PERCEIVED USEFULNESS, AND PERCEIVED PRICE ON THE PURCHASE INTENTION OF THE CUSTOMERS - Yusoff, Siti Khalidah Mohd; mohd shukri, Sakinah; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The goal connected with the present literature is to inspect the impact of trust, perceived usefulness, and perceived price on the purchase intension of the customers in Malaysia. Data were collected from the customer relation manager of the companies and SPSS employed to test the hypotheses. The outcomes demonstrated that positive connection among the trust and purchase intension, perceived usefulness and purchase intension, and perceived price and purchase intension.